Empowering Educators: Exploring Teacher Understanding and Implementation of Differentiated Instruction in Indonesian Primary Schools - Wiakta Putri, Ni Luh Vidary; Mangunsong, Frieda Maryam (Mimbar Sekolah Dasar, 2024)
Differentiated Instruction (DI) is recognized as an effective method for addressing varied student learning needs within a single classroom. However, integrating DI into teaching practices remains a challenge for many teachers. This non-experimental study employs a quantitative comparative design to examine the understanding and implementation of DI strategies among 330 in-service primary school teachers from 14 provinces in Indonesia, aged 22 to 60. The study utilized the Differentiated Instruction Scale, which was adapted into Bahasa Indonesia to ensure its relevance. The adaptation process followed the Guidelines for Cross-Cultural Adaptation of Self-Report Measures. Most respondents graduated from elementary school teacher education programs, with teaching experience spanning three months to 38 years. Results show that while teachers understand DI well, especially in the assessment category, implementation in product differentiation remains low. A significant gap exists between theoretical knowledge and practical application. Findings highlight the need for targeted professional development focusing on critical DI categories, especially Product differentiation. Recommendations stress the importance of structural support, ensuring teachers have the time and resources to develop varied learning products. Enhancing teachers' competence in DI is vital for meeting the diverse needs of students in Indonesian primary schools.